Ferreira Gullar numa perspectiva Foucaultiana: uma leitura de Em alguma parte alguma - RAULINO, Elaine Nascimento (2012)
Archaeological analysis of Ferreira Gullar s knowledge on a Foucauldian perspective: a reading of Em alguma parte alguma. This study aims to consider the identity, memorial and socio cultural traits on a poetic corpus, based on the main concepts: statements; set of statements (discourse); discourse formation; discourse practices; historical a priori; positivity; archaeological file of Faucault s knowledge; in addition to describing the poetic inscriptions or discursive elements brought into Brazilian socio cultural context; and interpret approach, the relations between Literature, Philosophy and History. To perform the analysis in this poetic phenomenon, a study corpus was built, consisting of 17 (seventeen) poems out of 59 (fifty nine). His initial hypothesis is the existence of heterogeneous metadiscursive in demonstrations and statements from within themselves to materialization of identity marks, memorials and sociocultural discourses poetic gullarianos. Among the problems, it s emphasized the importance of analyzing the materiality of the inscriptions that compose the set of poetic statements. The methodological approach is the bibliographic qualitative research outlined in the archaeological method, through triangulation technique of collecting and analyzing data. From the understanding and interpretation of the phenomenon under study, it is intended to show the integration possibility between Literature, Philosophy and History knowledges.